The art of war : the ancient classics - Tzu Sun, ....- (Chicester : Capstone Publishing Limited, 2017)
The original and bestselling leadership book! Sun Tzu's ideas on survival and success have been read across the world for centuries. Today they can still be applied to business, politics and life. The Art of War demonstrates how to win without conflict.
Keywords: Leiderschap